2016
DOI: 10.1016/j.aogh.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Related Cardiovascular Disease Burden in China

Abstract: B A C K G R O U N D With rapid economic development, urbanization, and an aging population, cardiovascular diseases (CVDs) have become the leading cause of death in China.O B J E C T I V E S The aim of this study was to provide a comprehensive review on the prevalence, awareness, treatment, and control of hypertension (HTN) as well as blood pressure (BP)-related morbidity and mortality of CVD in Chinese adults over time.F I N D I N G S The prevalence of HTN in China is high and increasing. Recent estimates are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 33 publications
4
91
0
1
Order By: Relevance
“…It is considered one of the major risk factors for the development of cardiovascular diseases such as stroke, ischemic heart disease, and heart failure. [14] Despite the recent advances in the development of antihypertensive therapeutic treatments and in the pathophysiology of hypertension, the prevalence of hypertension in China remains considerably high, whereas the rates of blood pressure (BP) control are notably low. The outline of the Report on Cardiovascular Disease in China (2014) demonstrated that the hypertension control (BP <140/90 mm Hg) rate was approximately 9.3% of all patients, and/or 27.4% of treated patients, although 42.6% of hypertensive patients in China were aware of their condition and 34.1% were receiving treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered one of the major risk factors for the development of cardiovascular diseases such as stroke, ischemic heart disease, and heart failure. [14] Despite the recent advances in the development of antihypertensive therapeutic treatments and in the pathophysiology of hypertension, the prevalence of hypertension in China remains considerably high, whereas the rates of blood pressure (BP) control are notably low. The outline of the Report on Cardiovascular Disease in China (2014) demonstrated that the hypertension control (BP <140/90 mm Hg) rate was approximately 9.3% of all patients, and/or 27.4% of treated patients, although 42.6% of hypertensive patients in China were aware of their condition and 34.1% were receiving treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes and alleles are expressed as number (percentage). * Represents the p<0.05.†P values was calculated using χ2 test of 3×2 contingency table for the genotype distribution and 2×2 contingency table for allele distribution. OR , 95% CI and p were calculated using logistic regression analysis (backward LR) with (§) and without (‡) adjusting for work sites, age, length of work, current smokers, current drinkers, BMI , FBG , TC , TG , HDL-C and LDL-C .…”
Section: Resultsmentioning
confidence: 99%
“…All other subjects without hypertension or other infections were defined as control group. Body weight and height were measured, and body mass index (BMI) was defined as the weight in kilograms divided by the height in metres squared (weight/height2). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of hypertension and high blood pressure are also increasing with its rapid development. A study showed that 33.6% (35.3% in men and 32% in women) or 335.8 million (178.6 million men and 157.2 million women) of the Chinese adult population had hypertension in 2010 [38]. Since China is major country for most of the production of materials and part required by all over the world, we see a lot of large scale industries and factories, few of the studies done in different cities of China are given below for a brief acknowledgement of occupational noise and prevalence of hypertension in China.…”
Section: Noise and Hypertensionmentioning
confidence: 99%